Comparison of effectiveness and cost for different HIV screening strategies implemented at large urban medical centre in the United States. Issue 10 (29th October 2020) - Skaathun, Britt; Pho, Mai T; Pollack, Harold A; Friedman, Samuel R; McNulty, Moira C; Friedman, Eleanor E; Schmitt, Jessica; Pitrak, David; Schneider, John A
Abstract: Introduction: Incident HIV infections persist in the United States (U.S.) among marginalized populations. Targeted and cost‐efficient testing strategies can help in reaching HIV elimination. This analysis compares the effectiveness and cost of three HIV testing strategies in a high HIV burden area in the U.S. in identifying new HIV infections. Methods: We performed a cost analysis comparing three HIV testing strategies in Chicago: (1) routine screening (RS) in an inpatient and outpatient setting, (2) modified partner services (MPS) among networks of the recently HIV infected and diagnosed, and (3) a respondent drive sampling (RDS)‐based social network (SN) approach targeting young African‐American men who have sex with men. All occurred at the same academic medical centre during the following times: routine testing, 2011 to 2016; MPS, 2013 to 2016; SN: 2013 to 2014. Costs were in 2016 dollars and included personnel, HIV testing, training, materials, overhead. Outcomes included cost per test, HIV‐positive test and new diagnosis. Sensitivity analyses were performed to assess the impact of population demographics. Results: The RS programme completed 57, 308 HIV tests resulting in 360 (0.6%) HIV‐positive tests and 165 new HIV diagnoses (0.28%). The MPS completed 146 HIV tests, resulting in 79 (54%) HIV‐positive tests and eight new HIV diagnoses (5%). The SN strategy completed 508 HIV tests, resulting in 210 (41%) HIV‐positive tests and 37 new HIV diagnoses (7.2%). Labour accounted for the majority of costs in all strategies. The estimated cost per new HIV diagnosis was 16, 773 for the RS programme, 61, 418 for the MPS programme and 15, 683 for the SN testing programme. These costs were reduced for the RS and MPS strategies in sensitivity analyses limiting testing efficacy to the highest prevalence patient populations (2, 841 and 33, 233 respectively). Conclusions: The SN strategy yielded the highest proportion of new diagnoses, followed closely by the MPS programme. Both the SN strategy and RS programme were comparable in the cost per new diagnosis. A simultaneous approach that consists of RS in combination with SN testing may be most effective for identifying new HIV infections in settings with heterogeneous epidemics with both high rates of HIV prevalence and HIV testing.